Do Brand Development Touchpoints Influence Private Higher Education Institutions’ Brand Equity? - Nursito, Sarwono (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2022)
Privately-managed higher education institutions that play a notable role in the Indonesian higher education sector, in today's increasingly competitive environment, need to develop brand equity to secure the existence and ensure the institutions' sustainability. Therefore, this study aims to examine the effect of brand development at the pre-admission touchpoint, during the course touchpoint, and the post-passing touchpoint on the brand equity of private higher education institutions. This study involved 100 third-year students from two private higher education institutions in Klaten Regency and used the purposive sampling methode as the sampling technique. The collected data were then analyzed using multiple linear regression analysis. The results indicated that brand development at the pre-admissions touchpoint becamee the primary variable in determining the brand equity of the private higher education, followed by brand development at the course touchpoint and brand development at the post-passing touchpoint. In addition, brand development at the three touchpoints simultaneously had a positive and significant influence on the brand equity of private higher education institutions.